Pengaruh literasi keuangan, inklusi keuangan dan financial technology terhadap perilaku keuangan pelaku UMKM di Kecamatan Sekupang - Eka Nur Anisyah; Dahlia Pinem; Siti Hidayati (MBR (Management and Business Review), 2021)
This research is using a descriptive quantitative study that aims to see and analyze the influence of financial literacy, financial inclusion, and financial technology on the financial behavior of SMEs in Sekupang District. This research uses a sample of 54 MSME actors in Sekupang District, Batam City. Smart PLS 3.0 Software are used on the Hypothesis testing and data processing to achieved number that can be analyze. The results obtained from the examiners are there is a significant effect of financial literacy on financial behavior, there is no significant effect of financial inclusion on financial behavior, there is no significant effect of financial technology on financial behavior.